2006
DOI: 10.1007/s00125-005-0112-4
|View full text |Cite
|
Sign up to set email alerts
|

Metformin improves atypical protein kinase C activation by insulin and phosphatidylinositol-3,4,5-(PO4)3 in muscle of diabetic subjects

Abstract: Aims/hypothesis: Metformin is widely used for treating type 2 diabetes mellitus, but its actions are poorly understood. In addition to diminishing hepatic glucose output, metformin, in muscle, activates 5'-AMP-activated protein kinase (AMPK), which alone increases glucose uptake and glycolysis, diminishes lipid synthesis, and increases oxidation of fatty acids. Moreover, such lipid effects may improve insulin sensitivity and insulinstimulated glucose uptake. Nevertheless, the effects of metformin on insulin-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 42 publications
(88 reference statements)
2
41
2
Order By: Relevance
“…55 In type 2 diabetic patients, metformin increases PKC-activity, accompanied by increased AMPK activity. 56 We have also demonstrated that PKC-phosphorylates LKB1 at Ser428 in both in vitro assays and in cultured cells, including endothelial cells, pericytes, adipocytes, and cultured vascular smooth muscle cells. 36 Furthermore, inhibition of PKC-attenuates AMPK activation by other stimuli (Z.X., unpublished data, 2008).…”
Section: Xie Et Almentioning
confidence: 63%
“…55 In type 2 diabetic patients, metformin increases PKC-activity, accompanied by increased AMPK activity. 56 We have also demonstrated that PKC-phosphorylates LKB1 at Ser428 in both in vitro assays and in cultured cells, including endothelial cells, pericytes, adipocytes, and cultured vascular smooth muscle cells. 36 Furthermore, inhibition of PKC-attenuates AMPK activation by other stimuli (Z.X., unpublished data, 2008).…”
Section: Xie Et Almentioning
confidence: 63%
“…Indeed, PKCζ/LKB1 signalling was also induced in Prep1-deficient mouse liver. Work by Luna and co-workers has demonstrated that metformin-induced activation of AMPK is accompanied by induction of PKCζ [38]. Importantly, genetic ablation as well as pharmacologic inhibition of PKCζ prevent stimulation of both LKB1 and AMPK [29], indicating that PREP1 lipogenic signalling upstream of AMPK involves PKCζ upregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with metformin increased insulin-induced Akt phosphorylation in cultured HepG2 cells [52] and HGL5 cells [53], as well as in vivo in rat heart [54]. In contrast, metformin reduced Akt phosphorylation stimulated by interleukin-1b or by high glucose [55], whereas Akt phosphorylation was unaltered by metformin treatment in H4IIE cells [56] and in vivo in diabetic muscle [57][58][59]. These mixed results with metformin indicate that context (i.e., cell type and stimulus) as well as possible multiple targets of metformin cause this diversity of effects on Akt phosphorylation.…”
Section: Discussionmentioning
confidence: 99%